Next generation converged media network architecture - Wenjun ZHANG; Yunfeng GUAN; Dazhi HE; Zhiyong CHEN; Li SONG; Yiling XU; Bin XIA (Tongxin xuebao)
In order to cope with the huge impact of the integration of media and network on the broadcast and mobile communication networks that carry media services,and the new requirements for network transmission efficiency,capacity expansion,resource utilization and service quality of new converged media services,a new generation media network system architecture for the development of converged media was proposed based on the summary of media development and network evolution in the past two decades.The new architecture can meet the application requirements of denser connectivity,higher reliability,lower latency and better interactivity.